Heart Rate and its Variability Assessed by Spectral Analysis in Elderly Subjects with Orthostatic Hypotension: A Case-Control Study - Rose Mary Ferreira Lisboa da Silva; Carlos Eduardo de Souza Miranda; Maira Tonidandel Barbosa; Maria Aparecida Camargos Bicalho (Arquivos Brasileiros de Cardiologia, 2018)
Abstract Background: The prevalence of orthostatic hypotension (OH) increases with age and is associated with changes in autonomic regulation of blood pressure (BP) and heart rate (HR). Objective: to assess HR and HR variability (HRV) in elderly subjects with OH and determine OH predictors. Methods: a total of 105 patients aged ≥ 60 years, 39 with OH (case group) and 66 without OH (control group) (age-matched) were studied. Patients underwent clinical assessment, electrocardiogram, biochemistry tests and Holter monitoring for spectral analysis of HRV (Fourier transform) in the supine and orthostatism positions to identify low frequency (LF) and high frequency (HF) components, as well as the LF/HF ratio. Results: median age was 73.0 years, 64 patients were women. In all participants, there was a reduction in HF (133.0 versus 76.0 ms2, p = 0.001) and increase in LF/HF (1.6 vs 2.1; p < 0.001) and no change in LF (233.0 versus 218.0 ms2, p = 0.080). Between-group comparisons revealed significant differences in the median values of HR in the supine position (62.0 vs. 69.0 bpm, p = 0.001) and LF in the supine position (157.0 in case group vs. 275.0 ms2 in the control group, p = 0.014). Spearman’s correlation coefficient of 0.27 was found between the groups. Multivariate analysis revealed that HR in the supine position was an independent variable for OH (p = 0.001- 95%CI = -0.022 and -0.006). Using the operating characteristic curve, the best cutoff point was 61 bpm, with a sensitivity of 77.3% and specificity of 51.3%, positive predictive value of 61.3%, and negative predictive value 69.3%. Odds ratio was 3.23 for OH in patients with a HR lower than 61 bpm. Conclusions: lower LF and HR in the supine position were found in patients with OH, regardless of age and gender. The independent predictor for OH was HR in the supine position, with an odds ratio of 3.23 for values lower than 61 bpm.